Growth hormone and insulin-like growth factors in fish Where we are and where to go - Reinecke, Manfred (2014)
This communication summarizes viewpoints, discussion, perspectives, and questions, put forward at a workshop on “Growth hormone and insulin-like growth factors in Wsh” held on September 7th, 2004, at the 5th International Symposium on Fish Endocrinology in Castellón, Spain.